Separation of 1-dodecanol and n-tetradecane through supercritical extraction. - Bonthuys, Gert Johannes Kotze (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Process Engineering))--Stellenbosch University, 2008.